ChatGPT and Its Possible Impact on Library Reference Services. - Chen, Xiaotian (Internet Reference Services Quarterly)
This column reports a simple test of ChatGPT with some library reference prompts and article writing prompts in February 2023, and compares the answers from traditional library chatbots with ChatGPT's. It also tries to call attention to possible lessons the library community may want to learn from previous transformative technology changes such as Google and Web 2.0.